The Importance of microRNAs in RAS Oncogenic Activation in Human Cancer - Roncarati, Roberta; Lupini, Laura; Shankaraiah, Ram C.; Negrini, Massimo (Frontiers in Oncology, 2019)
microRNAs (miRNAs) regulate gene expression by modulating the translation of protein-coding RNAs. Their aberrant expression is involved in various human diseases, including cancer. Here, we summarize the experimental pieces of evidence that proved how dysregulated miRNA expression can lead to RAS (HRAS, KRAS, or NRAS) activation irrespective of their oncogenic mutations. These findings revealed relevant pathogenic mechanisms as well as mechanisms of resistance to target therapies. Based on this knowledge, potential approaches for the control of RAS oncogenic activation can be envisioned.